Oscillations and change of sign in indirect exchange coupling of Fe/Au/Tb trilayer structures - Shypil, Elena; Pogorily, Anatoly; Podyalovsky, Dmitriy (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
Indirect exchange coupling between Fe and Tb layers through an Au layer showed oscillatory behavior with the thickness of the nonmagnetic metal. Different experimental tools such as polar magneto-optical Kerr effect, ferromagnetic resonance, and magnetotransport were used to investigate Fe/Au/Tb trilayers with Au thickness varying from 0 to 3.5 nm, prepared in an MBE system. From the experimental data we reconstruct the dynamics of the Fe and Tb magnetic moments with increasing thickness of the Au interlayer and show for the first time that there is a change of sign in the interaction between Fe and Tb, which is observed experimentally.